2021
DOI: 10.1097/sla.0000000000005087
|View full text |Cite
|
Sign up to set email alerts
|

“I Prefer to Stay Away”: A Qualitative Study of Patients in an Opioid-Sparing Pain Management Protocol

Abstract: Objective: The aim of this study was to explore beliefs and behaviors of opioid pain medications among patients undergoing elective surgery. Background: Opioid dependence after surgery is a major contributor to the ongoing opioid epidemic. Recent efforts by surgeons and health systems have sought to improve the education patients receive regarding safe opioid use after surgery; however, little is known about patients’ pre-existing beliefs surrounding opioids. Methods: Semistructured interviews were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(22 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…As a result, patients are willing to limit their opioids following surgery and this creates an environment for successfully implementing prescribing reduction initiatives. Similar to our study, another qualitative study among surgical patients revealed widespread awareness among patients about opioid medications which informed their intentions about using opioids [ 49 ]. Ultimately, the patients within our study reported that they were satisfied with their pain management.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, patients are willing to limit their opioids following surgery and this creates an environment for successfully implementing prescribing reduction initiatives. Similar to our study, another qualitative study among surgical patients revealed widespread awareness among patients about opioid medications which informed their intentions about using opioids [ 49 ]. Ultimately, the patients within our study reported that they were satisfied with their pain management.…”
Section: Discussionsupporting
confidence: 84%
“…The attitudes related to pain management were also an interesting finding that needs to be addressed. In a qualitative study by Johnson et al (2023) exploring the perceptions and behaviors of patients undergoing elective surgery in relation to opioid pain management, the respondents turned out to have conflicting intentions and opinions regarding postoperative opioid usage, despite being aware of the negative side effects. This was similar to the findings presented in our study in the subcategory confidence in but awareness of opioids .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 437 participants were included in 10 studies. The majority of studies were qualitative (n ¼ 9) 19,[43][44][45][46][47][48][49][50] with one retrospective cohort study with a mixed method approach. 18 Studies were conducted in the UK (n ¼ 2), 19,47 the USA (n ¼ 4), 18,46,48,50 Canada (n ¼ 1), 49 Denmark (n ¼ 1), 43 Sweden (n ¼ 1) 44 and Iran (n ¼ 1).…”
Section: Descriptions Of All Included Publicationsmentioning
confidence: 99%
“…45 Most of the studies (n ¼ 9) 19,[43][44][45][46][47][48][49][50] collected data through interviews and one study used an open-ended survey. 18 The time from surgery to interview varied, from within 48 to 72 h after surgery (n ¼ 1), 45 1 week (n ¼ 1), 18 2 to 4 weeks (n ¼ 1), 47 60 days (n ¼ 1), 48 90 days (n ¼ 1) 50 and They had pre-operative intentions to avoid using opioids for their pain management. Because of their opioid perceptions of abuse, overdose or addiction.…”
Section: Descriptions Of All Included Publicationsmentioning
confidence: 99%
See 1 more Smart Citation